1985
DOI: 10.2134/agronj1985.00021962007700030024x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato Response to K and P Fertilization1

Abstract: Limited literature is available to provide recommendations of K source and rate and P rate for sweet potato [Ipomoea batatas (L.) Lam.] production. Many growers, therefore, continue to use the more expensive sulfate (SO4) source of K rather than chloride (Cl) and higher than recommended rates of K and P. Accordingly, on‐farm experiments were conducted during 3 years on North Carolina Paleudults to determine effects of K source and rate and Prate on sweet potato yield, grade, and quality. Potassium sources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…In 2001, N concentrations exceeded the N sufficiency range defined by NCDA (3.2% to 4.0%) and were ranked ''high'' or in ''excess'' according to NCDA guidelines. In 2002 and2004, N concentrations were within sufficiency ranges for all systems and were similar to those observed for 'Jewel' by Nicholaides et al (1985) and Hammett et al (1984).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In 2001, N concentrations exceeded the N sufficiency range defined by NCDA (3.2% to 4.0%) and were ranked ''high'' or in ''excess'' according to NCDA guidelines. In 2002 and2004, N concentrations were within sufficiency ranges for all systems and were similar to those observed for 'Jewel' by Nicholaides et al (1985) and Hammett et al (1984).…”
Section: Resultssupporting
confidence: 87%
“…The Mehlich-3 extraction used in analysis can overestimate the amount of soil P that might be available for crop uptake. However, the P content present in all treatments is clearly higher than sweetpotato requirements (Nicholaides et al, 1985). Cover crops in Mean separation within column and year by Fisher's protected LSD (P # 0.05).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…biomass of which II2 kg ha-I was released within eight weeks (Hartemink & O'Sullivan, 2001). Sweet potato has a high demand for K (George et a!., 2002;Nicholaides et a!., 1985) and K influences tuber yield via increased dry matter allocation to the tubers and an increase in number of tubers per plant (Bourke, 1985a). Sweet potato has generally a low demand for P (Hahn & Hozyo, 1984) and as the soils had fair amounts of available P, the recycling of P by the fallow crop had possibly little effect on sweet potato yield.…”
Section: Nutrientmentioning
confidence: 99%
“…By comparison, increases in yield and quality of sweet potato (Ipomoea batatas L.) were not influenced by K source. In general, K fertilization increased the frequency of large tuberous roots in this species and slowed weight losses in storage; an index of quality (Nicholaides et al 1985). In a 13 site-year study where the addition of K to N-and P-fertilized soil more than doubled tuber yields, John et al (2013) reported increased tuber yield and a slight increase in tuber starch concentration for cassava (Manihot esculenta Crantz) with K fertilizer application.…”
Section: Tubers and Tuberous Rootsmentioning
confidence: 97%